The female suffering body : illness and disability of modern Arabic literature - Hamdar, Abir (Gender, culture, and politics in the Middle East., 2014)
Examines the absence of representations of female illness in Arab literature, exploring how both literary and cultural perspectives on female sickness and disability have transformed in the modern period and finds that over the course of 60 years women with physical ailments have moved from the margins to the center of Arabic literature.